Surface analysis of the solid electrolyte interface formed by additives on graphite electrodes in Li‐ion batteries using XPS, FE‐AES, and XHR‐SEM techniques. (22nd May 2014) - Lee, Seon‐Hong; Jo, Ie‐Su; Kim, Jake
<x xml:space="preserve">Abstract</x> We investigate the formation and distribution of the solid electrolyte interface (SEI) layer on a graphite anode with two additives [vinylethylene carbonate (VEC) and vinylene carbonate (VC)] in a formation process using XPS, field emission AES, and extreme high‐resolution SEM (XHR‐SEM) techniques, and we studied what factors play an important role in determining the formation of the SEI layer. The VEC‐derived SEI behaviors (morphology, thickness, compound, and balance over electrode position) on a graphite anode largely depend on the elevated temperature. The VC‐derived SEI layer is mostly formed in the initial charging step, showing simple growth (formation) behavior. It is suggested that the properties of the additives are important for SEI bonding configurations at the nanoscale film surface, and to achieve the stable SEI layer, there appears to be an effective formation process for the additive properties. This research highlights the challenges of developing a stable SEI layer with additives in the formation process for electric vehicle batteries and would make a contribution to the understanding of how formation conditions affect an SEI layer with respect to additive properties. Copyright © 2014 John Wiley & Sons, Ltd.